Internalisasi Nilai-Nilai Aswaja NU Dalam Kegiatan Keagamaan Di SMKN Jatiluhur Purwakarta - Mulyana, Arip; Asy’ari, Hasyim; Sirojuddin, Akhmad (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research aims to examine efforts to internalize Aswaja Nahdlatul Ulama (NU) values ??in religious activities at SMKN Jatiluhur, Purwakarta. A qualitative approach using the case study method was used to explore the concept and process of internalizing Aswaja NU values, especially tawassuth (moderate), tawazun (balanced), i'tidal (fair), and tasamuh (tolerant). Data was collected through interviews, observation and documentation. Research findings reveal that Jatiluhur Vocational School seeks to internalize the values ??of Aswaja NU through religious activities such as lectures, congregational prayers, reading the Koran, and commemorating Islamic holidays. The internalization process is carried out in stages, including Aswaja Knowing (providing understanding), Aswaja Feeling (growing a sense of the importance of Aswaja NU values), and Aswaja Action (implementing values ??in real action). This research also confirms the importance of role models from the entire academic community in the internalization process. Even though it does not have a specific written design, Jatiluhur Vocational School integrates NU Aswaja values ??into existing religious activities in an effort to prevent radicalism and build a moderate and tolerant character. The findings of this research contribute to strengthening moderate and tolerant religious education in the school environment to prevent the spread of radical ideas and promote diversity.